Adult Jokes in Sausage Party Movie: A Study of Multimodality - Firmansyah, Muhammad Wahyu; Ariyanti, Lisetyo (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2021)
The Sausage Party Movie is a comedy film directed by Conrad Vernon and Greg Tiernan (2016) which is sensational. The theme brings some controversy among people about how vulgar it is. The story exposed some sensitive themes such as intercourse, orgy, homosexuality, bisexuality, foreplay, torturing, murderer, annihilation, genocide, colonial domination, and other aspects as well. The contested scenes in the movie which manifest adult jokes are being analyzed by investigating the visual and linguistic elements related to the particular scenes. Thus, this study analyzed the adult jokes in “Sausage Party” by using multimodality approach which combines types of metafunction from Systemic Functional Linguistic (SFL) and visual elements of Gunther Kress and Theo van Leeuwen framework. The data were all scenes which contain adult jokes in this movie. The result reveals that some scenes may construct the meaning which related with the adult jokes. Despite the fact that this film is a comedy cartoon which associated with children, many adult jokes are being displayed to entertain the audiences which not suitable for underage communities. Likewise, the adult jokes are displayed as implicitly as possible to entertain either the underage who thinks it is only a usual joke or the adulthood who socially and practically understood the meaning behind it. In addition, the data is occupied by an intercourse activity between sausage and bun, torturing and murdered ideas, and also the idea of how human had intercourse from another perspective.